Слов’янська ода Пантелеймона Куліша - Шупик, В. (Слово і Час, 2010)
У статті йдеться про основні громадсько-політичні концепції П. Куліша. Авторка описує естетизацію горя П.Кулішем у поезії “Слов’янська ода” (1882), поетичній збірці “Дзвін” (1893). The paper surveys the most important concepts of politics and public life developed by P. Kulisch. In particular, the author focuses on the aesthetization of grief in P. Kulish’s “Slavic Ode” (1882), and in his collection of poems “The Chime” (1893). В статье идет речь об основных концепциях П.Кулиша. Автор описывает эстетизацию горя П. Кулишом в стихотворении “Слов’янська ода” (1882), поэтическом сборнике “Дзвін” (1893).